KAJIAN INTERACTION DESIGN WEBSITE MUSEUM RANGGAWARSITA SEMARANG - Erisa Adyati Rahmasari; Toto Haryadi (TANRA: Jurnal Desain Komunikasi Visual Fakultas Seni dan Desain Universitas Negeri Makassar, 2022)
Websites have important function in the IoT era, especially in tourism field. One of them is the Ranggawarsita museum, which launched a website to anticipate less of visitors during the pandemic. On the other hand, form online media user community appears stereotypes regarding websites managed by the government are of worst quality, both in terms of content presentation and website aesthetics in terms of appearance, color, and layout. This is a main problem which must be followed up to avoid negative image, especially for educational tourism. This research was conducted to examine and analyze the characteristic of Ranggawarsita’s museum website and to prove its quality referring to both Interaction Design and 9 criterias for a good website theory. The author uses qualitative method which is supported by observation, literature study, and semi-open questionnaire. The content analysis method was chosen to find the characteristics of Ranggawarsita’s museum website in order to produce an in-depth analysis according to used theory. The results of this study are the quality of ergonomics, appearance, content, access and feedback on the Ranggawarsita’s museum website, which can be used as advice to museum and other institutions in order to develop websites that suit user needs.